O ensino de literatura em Boa Vista-RR: "aprendizagem literária nas escolas de Ensino Médio" - Santos, Herica Maria Castro dos (2012)
The several national evaluation systems like ENEM, SAEB, among others, are demonstrating, along the years, a sad picture of the Brazilian education, the students' of the country failure in to read and to interpret the several types of texts. With respect to the Medium Teaching, the picture is still more desperate, such the deficiency that the students present in front of the several literary studies. It is evident that a great portion of the students has not been learning the necessary knowledge for an understanding, at reasonable least, of literary understanding. This fact demonstrates the incompetence of the school in forming readers with complex abilities of reading, as the analysis, the comparison and the interpretation. The school has been stopping motivating the students' reading, “the reading habit” is a sentence that doesn't appear in the adolescents' of Medium Teaching daily context. This research focused mainly the paper of the largest stimulator that we have at the school: the teacher. To assist to the objective of the research 21 schools of Medium Teaching were visited to regulate, with more than 80 teachers in the disciplines Portuguese Language and Literature. The distance among the several schools, as much the central ones as the outlying ones demanded many days of departures and arrivals in the most distant neighborhoods in search of teachers that they were disposed to answer the questionnaire of the research, that it had as objective to investigate the teaching of Literature. Initially I present a theoretical study on the teaching of the Literature, describing the conceptions of the teaching and a brief historical retrospective look. In the sequence I describe what the documents of the teaching of Literature governs in the last years and, at the end, I present the collected data and I point possible suitable solutions for the own teachers.